Answer:
The factorized expression is (-5) × (t - 2.747) ×(t - 1.747)
Explanation:
The given expression is -5·t² + 5·t + 24
To factorize the expression by completing the square method, we equate the expression to zero to get;
-5·t² + 5·t + 24 = 0
WE divide by -5 to get;
t² - t - 24/5 = 0
t² - t = 24/5
t² - t + 1/4 = 24/5 + 1/4
(t - 1/2)² = 5.05
t - 1/2 = ±√5.05
t = 1/2 + √5.05, 1/2 - √5.05
The factorized expression becomes;
(t - 1/2 + √5.05) and (t - 1/2 - √5.05)
Which gives;
(t - 2.747) ×(t - 1.747)
The factorized expression is (-5) × (t - 2.747) ×(t - 1.747).